The p21‐activated kinase 2 (PAK2), but not PAK1, regulates contraction‐stimulated skeletal muscle glucose transport - Møller, Lisbeth L. V. (Physiol Rep, 2020)
AIM: Muscle contraction stimulates skeletal muscle glucose transport. Since it occurs independently of insulin, it is an important alternative pathway to increase glucose transport in insulin‐resistant states, but the intracellular signaling mechanisms are not fully understood. Muscle contraction activates group I p21‐activated kinases (PAKs) in mouse and human skeletal muscle. PAK1 and PAK2 are downstream targets of Rac1, which is a key regulator of contraction‐stimulated glucose transport. Thus, PAK1 and PAK2 could be downstream effectors of Rac1 in contraction‐stimulated glucose transport. The current study aimed to test the hypothesis that PAK1 and/or PAK2 regulate contraction‐induced glucose transport. METHODS: Glucose transport was measured in isolated soleus and extensor digitorum longus (EDL) mouse skeletal muscle incubated either in the presence or absence of a pharmacological inhibitor (IPA‐3) of group I PAKs or originating from whole‐body PAK1 knockout, muscle‐specific PAK2 knockout or double whole‐body PAK1 and muscle‐specific PAK2 knockout mice. RESULTS: IPA‐3 attenuated (−22%) the increase in glucose transport in response to electrically stimulated contractions in soleus and EDL muscle. PAK1 was dispensable for contraction‐stimulated glucose transport in both soleus and EDL muscle. Lack of PAK2, either alone (−13%) or in combination with PAK1 (−14%), partly reduced contraction‐stimulated glucose transport compared to control littermates in EDL, but not soleus muscle. CONCLUSION: Contraction‐stimulated glucose transport in isolated glycolytic mouse EDL muscle is partly dependent on PAK2, but not PAK1.